MAPPING OF GENES INCOMPATIBILITY (inc) OF THE R906 PLASMIDE (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
Localization of genes incompatibility (inc) on the DNA R906 plasmide map is fulfilled through revealation of P-1 specific incompatibility by various deletion and recombination derivatives of R906 plasmide. It has been carried out by the analyses of segregation kinetics in the case of combining the above mentioned derivatives in a cell as a result of their reciprocal transformation or conjugation with Inc P-1 plasmides R751 and R702. It has become possible to localize inc genes on the DNA sector with 24.6–25.7 kb coordinates comparing the received data with the restriction maps of the derivatives of R906 plasmide.
Keywords: P-1 specific incompatibility; deletion and recombination derivatives; R906 plasmide; segregation kinetics